Enhanced electrochemical energy storage properties of carbon coated Co3O4 nanoparticles-reduced graphene oxide ternary nano-hybrids. Issue 11 (1st August 2020) - Aadil, Muhammad; Zulfiqar, Sonia; Sabeeh, Humera; Warsi, Muhammad Farooq; Shahid, Muhammad; Alsafari, Ibrahim A.; Shakir, Imran
Abstract: In this article, we have synthesized carbon-coated cobalt oxide nanoparticles (NPs) and their nanocomposite with reduced graphene oxide (C@Co3 O4 /r-GO) via chemical and ultrasonication techniques. The observed higher electrical conductivity (1.4 × 10 −3  S/m) of the nanocomposite than the pristine NPs (1.9 × 10 −8  S/m) was due to the combined effect of the carbon-coating and r-GO nanosheets. The higher specific surface area (118 m 2 /g) of the nanocomposite was due to the relived agglomeration of the NPs via the carbon-coating and r-GO matrix. The nanocomposite based electrode shows exceptional gravimetric capacitance of 674 F/g at 1 A/g and loses just 18% of its initial capacitance after 10 3 charges/discharge cycles. The superior electrochemical performance of the nanocomposite was due to its higher surface area and synergistic improvements between carbon-coated NPs and highly conductive r-GO nanosheets. In the nanocomposite, the r-GO nanosheets play a double role to increase the energy storage properties. For example, the r-GO sheets acted as a capacitive supplement as well as a conductive matrix for a speedy redox reaction. Highly conductive nanocomposite also showed lower charge transfer resistance (Rct ~ 12.78 Ω) during the electrochemical impedance spectroscopic (EIS) tests that further facilitated the redox reaction to achieve higher pseudocapacitance. The observed electrical and electrochemical results demonstrate the potential of the C@Co3 O4 /r-GO nanocomposite for hybrid supercapacitors.